Combination of TRP channel dietary agonists induces energy expending and glucose utilizing phenotype in HFD-fed mice - Kaur, Jasleen; Kumar, Vijay; Kumar, Vibhu; Shafi, Sadiah; Khare, Pragyanshu; Mahajan, Neha; Bhadada, Sanjay K.; Kondepudi, Kanthi Kiran; Bhunia, Rupam Kumar; Kuhad, Anurag; Bishnoi, Mahendra (International Journal of Obesity, 2021)
Background Bioactive dietary constituents activating Transient receptor potential (TRP) channels have emerged as promising candidates for the prevention of metabolic disorders. Objective The present study is an attempt to evaluate anti-obesity potential of a dietary TRP-based tri-agonist, combination of sub-effective doses of capsaicin (TRPV1 agonist), menthol (TRPM8 agonist), and cinnamaldehyde (TRPA1 agonist) in high-fat diet (HFD)-fed mice. Design Male C57BL/6 J mice divided into three groups (n = 8), were fed on normal pellet diet (NPD), or high-fat diet (HFD) (60% energy by fat) and HFD + CB (combination of capsaicin 0.4 mg/Kg, menthol 20 mg/Kg, and cinnamaldehyde 2 mg/Kg; p.o) for 12 weeks. Effects on HFD-induced weight gain, biochemical, histological and genomic changes in the WAT, BAT, liver and hypothalamus tissues were studied. Results Administration of tri-agonist prevented HFD-induced increase in weight gain, improved altered morphometric parameters, glucose homeostasis, and adipose tissue hypertrophy. Tri-agonist supplementation was found to induce browning of white adipose tissue and promote brown adipose tissue activation. Enhanced glucose utilization and prevention of lipid accumulation and insulin resistance in the liver was observed in mice supplemented with a tri-agonist. Conclusion The present work provides evidence that the new approach based on combination of sub-effective doses of TRP channel agonists (TRI-AGONIST) can be employed to develop concept-based functional food for therapeutic and preventive strategies against HFD-associated pathological complications.
CRIS-Team WoS Importer:2021-10-15

The TRPC5 receptor as pharmacological target for pain and metabolic disease - Khare, Pragyanshu; Chand, Jagdish; Ptakova, Alexandra; Liguori, Renato; Ferrazzi, Fulvia; Bishnoi, Mahendra; Vlachova, Viktorie; Zimmermann, Katharina (Pharmacology & Therapeutics, 2024)
The transient receptor potential canonical (TRPC) channels are a group of highly homologous nonselective cation channels from the larger TRP channel family. They have the ability to form homo- and heteromers with varying degrees of calcium (Ca2+) permeability and signalling properties. TRPC5 is the one cold-sensitive among them and likewise facilitates the influx of extracellular Ca2+ into cells to modulate neuronal depolarization and integrate various intracellular signalling pathways. Recent research with cryo-electron microscopy revealed its structure, along with clear insight into downstream signalling and protein-protein interaction sites. Investigations using global and conditional deficient mice revealed the involvement of TRPC5 in metabolic diseases, energy balance, thermosensation and conditions such as osteoarthritis, rheumatoid arthritis, and inflammatory pain including opioid-induced hyperalgesia and hyperalgesia following tooth decay and pulpitis. This review provides an update on recent advances in our understanding of the role of TRPC5 with focus on metabolic diseases and pain.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Calcium homeostasis; Energy expenditure; Glucose homeostasis; Inflammatory pain; Metabolism; TRPC5

Topical menthol, a pharmacological cold mimic, induces cold sensitivity, adaptive thermogenesis and brown adipose tissue activation in mice - Sankina, Polina; Lal, Roshan; Khare, Pragyanshu; von Hörsten, Stephan; Fester, Lars; Aggarwal, Vaishali; Zimmermann, Katharina; Bishnoi, Mahendra (Diabetes Obesity & Metabolism, 2024)
Aim: Brown adipose tissue (BAT) thermogenesis has profound energy-expanding potential, which makes it an attractive target tissue to combat ever-increasing obesity and its other associated metabolic complications. Although it is fairly accepted that cold is a potent inducer of BAT activation and function, there are limited studies on the mechanisms of pharmacological cold-mimicking agents, such as the TRPM8 agonist, menthol, on BAT thermogenesis and activation. Methods: Herein, we sought to determine the effect of topical application of menthol (10% w/v [4 g/kg] cream formulation/day for 15 days) on temperature sensitivity behaviour (thermal gradient assay, nesting behaviour), adaptive thermogenesis (infrared thermography, core body temperature), BAT sympathetic innervation (tyrosine hydroxylase immunohistochemistry) and activation (18F-FDG PET-CT analysis, Uncoupling Protein 1 immunohistochemistry and BAT gene expression), whole-body energy expenditure (indirect calorimetry) and other metabolic variables in male C57BL/6N mice. Results: We show that male C57BL/6N mice: (a) develop a warm-seeking and cold-avoiding thermal preference phenotype; (b) display increased locomotor activity and adaptive thermogenesis; (c) show augmented sympathetic innervation in BAT and its activation; (d) exhibit enhanced gluconeogenic capacity (increased glucose excursion in response to pyruvate) and insulin sensitivity; and (e) show enhanced whole-body energy expenditure and induced lipid-utilizing phenotype after topical menthol application. Conclusions: Taken together, our findings highlight that pharmacological cold mimicking using topical menthol application presents a potential therapeutic strategy to counter weight gain and related complications.
CRIS-Team Scopus Importer:2024-08-02
Keywords: brown adipose tissue; lipid utilizing; menthol; thermogenesis; topical; TRPM8